Characterization of fungal communities in house dust samples collected from central Portugal-a preliminary survey - Sousa, A. (2015)
House dust is a repository and concentrator of many chemical and biological agents including fungi. Considering that dust acts as a long-term reservoir of airborne fungi and that cumulative exposure is more relevant to potential health problems than single-day or short-term exposure, characterization of fungal communities in dust samples is of paramount importance. In the present study, the fungal composition of Portuguese house dust samples was determined. A total of 28 samples were obtained from vacuum cleaner deposits from households located in central Portugal. DNA was extracted from dust samples and fungal communities were analyzed using a culture-independent polymerase chain reaction (PCR)- denaturing gradient gel electrophoresis (DGGE) approach. Cultural analyses were also performed in order to identify the viable fungi species present in selected samples. Fungal diversity, reported as the number of operational taxonomic units (OTU), varied between 9 and 56 OTU. This analysis of viable fungi showed that Aspergillus was the most abundant genus, followed by Penicillium, Mucor, and Rhizomucor. Trichoderma, Chrysosporium, Fusarium, Rhizopus, and Stachybotrys were found in a limited number of houses. Our results demonstrated that dust is, in fact, home for a diverse and heterogeneous fungal community and that some of the species found are known allergic agents with severe negative impacts on human health.